Responses of Barley to High Ambient Temperature Are Modulated by Vernalization - Ochagavía, Helga; Kiss, Tibor; Karsai, Ildikó; Casas, Ana M.; Igartua, Ernesto (Frontiers in Plant Science, 2022)
Ambient temperatures are increasing due to climate change. Cereal crops development and production will be affected consequently. Flowering time is a key factor for adaptation of small grain cereals and, therefore, exploring developmental responses of barley to rising temperatures is required. In this work, we studied phasic growth, and inflorescence traits related to yield, in eight near isogenic lines of barley (Hordeum vulgare L.) differing at the VRN-H1, VRN-H2 and PPD-H1 genes, representing different growth habits. The lines were grown in contrasting vernalization treatments, under two temperature regimes (18 and 25°C), in long days. Lines with recessive ppd-H1 presented delayed development compared to lines with the sensitive PPD-H1 allele, across the two growth phases considered. High temperature delayed flowering in all unvernalized plants, and in vernalized spring barleys carrying the insensitive ppd-H1 allele, whilst it accelerated flowering in spring barleys with the sensitive PPD-H1 allele. This finding evidenced an interaction between PPD-H1, temperature and vernalization. At the high temperature, PPD-H1 lines in spring backgrounds (VRN-H1-7) yielded more, whereas lines with ppd-H1 were best in vrn-H1 background. Our study revealed new information that will support breeding high-yielding cultivars with specific combinations of major adaptation genes tailored to future climatic conditions.